Circulating Dickkopf‐1 in Diabetes Mellitus: Association With Platelet Activation and Effects of Improved Metabolic Control and Low‐Dose Aspirin. Issue 4 (18th July 2014) - Lattanzio, Stefano; Santilli, Francesca; Liani, Rossella; Vazzana, Natale; Ueland, Thor; Di Fulvio, Patrizia; Formoso, Gloria; Consoli, Agostino; Aukrust, Pål; Davì, Giovanni
Abstract : Background: Dickkopf‐1 (DKK‐1) is a major regulator of the Wnt signaling pathway, involved in inflammation, atherogenesis, and the regulation of glucose metabolism. Because platelets are major contributors to circulating levels of DKK‐1 in other clinical settings, we aimed at characterizing the platelet contribution to DKK‐1 in type 2 diabetes mellitus (T2DM) and evaluating associations of DKK‐1 with glucose metabolism, platelet activation, and endothelial dysfunction. Methods and Results: A cross‐sectional comparison of DKK‐1, soluble CD40L (sCD40L; reflecting platelet‐mediated inflammation), asymmetric dimethylarginine (ADMA; marker of endothelial dysfunction), and urinary 11‐dehydro‐thromboxane B2 (in vivo marker of platelet activation) was performed among 214 diabetic patients (90 receiving aspirin at 100 mg/day) and 30 healthy controls. Plasma DKK‐1 levels were markedly higher in patients with T2DM than in healthy patients ( P <0.0001). DKK‐1 levels were significantly lower in diabetic patients receiving compared with those not on aspirin treatment ( P =0.008); in the latter, DKK‐1 was significantly correlated with 11‐dehydro‐thromboxane B2, ADMA, and CD40L (ρ=0.303. P <0.0001, ρ=0.45. P <0.0001, and ρ=0.37, P <0.0001, respectively) but not with glycemic control or DM duration. Among patients not receiving aspirin, improvement of metabolic control in a subgroup of newly diagnosed patients treated with acarbose for 20 weeks and in a group treated with rosiglitazone for 24 weeks was associated with concurrent significant reductions in DKK‐1 ( P =0.005 and P =0.004) and 11‐dehydro‐thromboxane B2 ( P =0.005 and P =0.004). Conclusions: Circulating DKK‐1 is increased in T2DM and associated with endothelial dysfunction and platelet activation. Plasma DKK‐1 levels are reduced with improvement of glycemic control and low‐dose aspirin treatment.